Hydrothermal formation of tobermorite studied by in situ X-ray diffraction under autoclave condition - Kikuma, Jun (Journal of synchrotron radiation, 2009)
Hydrothermal formation of tobermorite from a pre-cured cake has been investigated by transmission X-ray diffraction (XRD) using high-energy X-rays from a synchrotron radiation source in combination with a newly designed autoclave cell. The autoclave cell has a large and thin beryllium window for wide-angle X-ray diffraction; nevertheless, it withstands a steam pressure of more than 1.2 MPa, which enables in situ XRD measurements in a temperature range of 373 to 463 K under a saturated steam pressure. Formation and/or decomposition of several components has been successfully observed during 7.5 h of reaction time. From the intensity changes of the intermediate materials, namely non-crystalline C-S-H and hydroxylellestadite, two pathways for tobermorite formation have been confirmed. Thus, the newly developed autoclave cell can be used for the analyses of reaction mechanisms under specific atmospheres and temperatures